2007
DOI: 10.1152/ajpheart.00977.2007
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 induction improves ischemic renal failure: role of nitric oxide and peroxynitrite

Abstract: The present study evaluated the effects of heme oxygenase-1 (HO-1) induction on the changes in renal outer medullary nitric oxide (NO) and peroxynitrite levels during 45-min renal ischemia and 30-min reperfusion in anesthetized rats. Glomerular filtration rate (GFR), outer medullary blood flow (OMBF), HO and nitric oxide synthase (NOS) isoform expression, and renal low-molecular-weight thiols (-SH) were also determined. During ischemia significant increases in NO levels and peroxynitrite signal were observed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 29 publications
4
46
0
Order By: Relevance
“…HO-1 produces carbon monoxide (a potent vasodilator) while degrading heme, which may preserve tissue blood flow during reperfusion (191). Thus, it has been suggested that the induction of HO-1 can protect the kidney from ischemic damage by decreasing oxidative damage and NO generation (192,193). Finally, in addition to its anti-apoptotic properties, EPO may restore renal microcirculation, and thus protect the kidney from ischemic damage (176), by stimulating the mobilization and differentiation of progenitor cells toward an endothelial phenotype (194) and inducing NO release from eNOS (195).…”
Section: Adaptation To Hypoxiamentioning
confidence: 99%
“…HO-1 produces carbon monoxide (a potent vasodilator) while degrading heme, which may preserve tissue blood flow during reperfusion (191). Thus, it has been suggested that the induction of HO-1 can protect the kidney from ischemic damage by decreasing oxidative damage and NO generation (192,193). Finally, in addition to its anti-apoptotic properties, EPO may restore renal microcirculation, and thus protect the kidney from ischemic damage (176), by stimulating the mobilization and differentiation of progenitor cells toward an endothelial phenotype (194) and inducing NO release from eNOS (195).…”
Section: Adaptation To Hypoxiamentioning
confidence: 99%
“…However, when present in excess, a condition known as oxidative stress, they exert deleterious effects including lipid peroxidation, oxidative DNA damage and protein oxidation and nitration that collectively lead to progressive endothelial and tubular cells damage described in the precedent section. Generation of high levels of reactive oxygen species during renal ischemia/reperfusion have been confirmed directly (Zweier et al, 1994;Salom et al, 2007) and indirectly by measuring the effects of oxidants on lipids, proteins and DNA and by determining the beneficial effects of free radicals scavenging with antioxidant enzymes like superoxide dismutase or catalase or with antioxidants allopurinol (a xanthine oxidase inhibitor), tempol (an superoxide dismutase mimetic), N-acetyl-L-cysteine (an antioxidant), or dimethylthiourea (a hydroxyl radical scavenger) (Chatterjee et al, 2000;López-Conesa et al, 2001;Noiri et al, 2001;Tsuji et al, 2009). However, these compounds also scavenge or inhibit the formation of peroxynitrite (ONOO¯) a highly reactive chemical specie derived from nitric oxide and superoxide.…”
Section: Free Radicals In Acute Renal Injurymentioning
confidence: 91%
“…HO-1 prior to the induction of I/R results in functional protection in ischemic renal failure (Maines, 1999), which is partially mediated by reduction of oxidative and nitrosative stress during ischemia (Salom et al, 2007). Moreover, in the same way that HO metabolites maintain renal medullary perfusion (Zou et al, 2000), glomerular filtration rate and renal blood flow (Arregui B, 2004) in physiological conditions, HO-1 induction preserved postischemic medullary blood flow and GFR, in ischemic renal failure, (Salom et al, 2007).…”
Section: Role Of Heme Oxygenase System In Renal I/rmentioning
confidence: 99%
See 2 more Smart Citations